The transition toward sustainable organic food systems in Indonesia: A case study of organic rice - Ardiansyah; David, Wahyudi (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2020)
The demand for organic food in Indonesia is increasing annually. Organic rice is one of the most consumed organic foods in Indonesia. Organic rice perceive as healthier than conventional rice; however, in the context of the food system (from farm to fork), is organic rice better than conventional rice? To what extent does the transition contribute to sustainability? We have been investigating organic rice in the context of the food system since 2016. Our experiment reveals that (1) organic rice fits the organic principle in the level of farming where less pesticide, better farmer income and protecting biodiversity (2) lower degree of milling in organic rice resulted in the highest nutritional benefit (3) consumer perception depend on nutritional information From this point of view, we conclude that organic rice would be fit for the organic food principle and sustainable way if the rice has a lower degree of milling.